2015
DOI: 10.1016/j.jpeds.2014.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Computational Gene Expression Modeling Identifies Salivary Biomarker Analysis that Predict Oral Feeding Readiness in the Newborn

Abstract: Objective-To combine mathematical modeling of salivary gene expression microarray data and systems biology annotation with RT-qPCR amplification to identify (phase I) and validate (phase II) salivary biomarker analysis for the prediction of oral feeding readiness in preterm infants.Study design-Comparative whole transcriptome microarray analysis from 12 preterm newborns pre-and post-oral feeding success was used for computational modeling and systems biology analysis to identify potential salivary transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…43,44 Another area under investigation involves the use of objective salivary biomarkers related to the neonate's developing brain and sensory and facial development in relation to oral feeding success. 45 In the future, these biomarkers may enable clinicians to determine when brain maturation supports the initiation of oral feeding and may increase our understanding of the mechanisms in the developing brain that underlie oral feeding readiness. 45 Investigations are needed to determine the long-term outcomes associated with feeding interventions as new technologies emerge.…”
Section: Clinic or Bedside Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Another area under investigation involves the use of objective salivary biomarkers related to the neonate's developing brain and sensory and facial development in relation to oral feeding success. 45 In the future, these biomarkers may enable clinicians to determine when brain maturation supports the initiation of oral feeding and may increase our understanding of the mechanisms in the developing brain that underlie oral feeding readiness. 45 Investigations are needed to determine the long-term outcomes associated with feeding interventions as new technologies emerge.…”
Section: Clinic or Bedside Assessmentmentioning
confidence: 99%
“…45 In the future, these biomarkers may enable clinicians to determine when brain maturation supports the initiation of oral feeding and may increase our understanding of the mechanisms in the developing brain that underlie oral feeding readiness. 45 Investigations are needed to determine the long-term outcomes associated with feeding interventions as new technologies emerge. Development of objective and reproducible noninvasive measures that enhance the clinical assessment is desperately needed.…”
Section: Clinic or Bedside Assessmentmentioning
confidence: 99%
“…Breast milk feeding is associated with an altered oral and nasopharyngeal microbiota later in infancy 6, 7 . However, oral feeding is not practical in most preterm infants due to developmental immaturity 8 . Recently, the practice of early (as soon as produced by the mother) oral administration of mother’s own colostrum was proposed as a protective strategy 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Current standards of care mandate the use of cue-based feeding protocols that ultimately lack the necessary specificity and sensitivity required to avoid placing infants at risk for choking, desaturation, and feeding aversion. Prior research has shown that for a newborn to successfully feed they must integrate numerous cranial nerves and muscles, along with their sensory, neurodevelopmental, and hunger signaling pathways (Barlow 2009;Maron et al 2015). Interestingly, in the original neonatal salivary transcriptome study, computational and systems biology reviews of gene targets highlighted biological pathways associated with feeding maturity.…”
Section: Translating the Transcriptome; Neonatal Applicationsmentioning
confidence: 99%
“…Computational analysis and systems biology review of the microarray data identified a panel of genes (n ¼ 24) that were involved in the diverse biological systems required in oral feeding maturation including sensory integration, facial development, neurodevelopment, hunger signaling, and digestive system development (Maron et al 2015). A large prospective validation phase testing each of these biomarkers, alone and in combination, on 400 saliva samples resulted in the further identification of five genes (NPY2R, WNT3, PLXNA1, NPHP4, and AMPK), that when combined with postconceptional age and sex had good accuracy at predicting feeding success in the newborn (area under the receiving operator curve ¼ 0.78).…”
Section: Translating the Transcriptome; Neonatal Applicationsmentioning
confidence: 99%